2015
DOI: 10.1111/bjet.12275
|View full text |Cite
|
Sign up to set email alerts
|

Survey of learning experiences and influence of learning style preferences on user intentions regarding MOOCs

Abstract: With the rapid development of web techniques, information and communication technology is being increasingly used in curricula, and learning portfolios can be automatically retrieved and maintained as learners interact through e-learning platforms.Further, massive open online courses (MOOCs), which apply such technology to provide open access to hundreds and thousands of learners, have recently gained popularity in higher education. Learning styles refer to an individual's approach to learning based on their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 14 publications
6
78
1
5
Order By: Relevance
“…These findings to some extent do not differ from previous studies that report skills development, exploration of areas of interest, and the desire to learn new concepts as motivating factors for learners to register in MOOCs (Chang et al, 2015). However, compared to other studies (Radford et al, 2015;Stokes, Towers, Jinks & Symington, 2015;Zhong et al, 2016), earning credits and the relationship with participants' program, which can be assimilated to educational pursuit in previous studies, are not as important as friends when it comes to stirring students to enroll into a MOOC.…”
Section: Employment Statuscontrasting
confidence: 63%
See 2 more Smart Citations
“…These findings to some extent do not differ from previous studies that report skills development, exploration of areas of interest, and the desire to learn new concepts as motivating factors for learners to register in MOOCs (Chang et al, 2015). However, compared to other studies (Radford et al, 2015;Stokes, Towers, Jinks & Symington, 2015;Zhong et al, 2016), earning credits and the relationship with participants' program, which can be assimilated to educational pursuit in previous studies, are not as important as friends when it comes to stirring students to enroll into a MOOC.…”
Section: Employment Statuscontrasting
confidence: 63%
“…Still, these studies on MOOC learners' motivation did not investigate the motivation of learners assigned to groups in MOOCs. Furthermore, unfamiliarity with online environments, preference for physical classroom, lack of face-to-face interactions, absence of real group discussion time, and fear of MOOCs operation were also identified in the literature as main reasons for not enrolling in a MOOC (Chang et al, 2015). Chang et al (2015) study seems to suggest that creating groups, establishing interactions within MOOCs, and learners' familiarity with online environments can motivate students to participate in a MOOC.…”
Section: Motivation For Enrollingmentioning
confidence: 96%
See 1 more Smart Citation
“…The condition of learners must be in line so that the policy of the institution. G aya learn students with character innovators as the basis for managing students from every generation [29], [31]- [35]. The development of the study of learning styles shows the development of more than 70 learning styles reported in hundreds of published studies from the educational and psychological research literature.…”
Section: A Learner's Behaviormentioning
confidence: 99%
“…Similarly, there is the study by Chang, Hung, and Lin (2015) who researched the communication channels with the objec tive of reducing dropout rates and finding methods for encouraging participation on MOOC courses. These authors state that «giving students more opportunities for group study can also improve their parti cipation as solution to problems and ideas can be inspired through discussions with other students» (Chang, Hung, and Lin, 2015 p. 539).…”
Section: Communicationmentioning
confidence: 99%